The Constitutional Court's Ruling Prevents the Potential Exploitation of Zakat as A Profit Commodity from The Perspective of Sharia Economics - Ade Sofyan Mulazid; Ade Ananto Terminanto; Suhendra Suhendra; Supriyono Supriyono; Athia Nur Kamila; Yunia Silvia Sesunan (Jurnal Pemberdayaan Masyarakat, 2026)
This research aims to analyze how the Constitutional Court's decision on zakat safeguards it from the risk of becoming a commodity and to emphasize that sakti constitutional law must be integrated into zakat management. We employ a Systematic Literature Review (SLR) methodology for PMI studies, following PRISMA criteria. From a total of 84 articles, after filtering and reviewing the abstracts, the database exclusion process left 45 relevant articles, which were divided and analyzed into themes typical of Islamic economics, including zakat management, Islamic law, and zakat protection. This study concludes that the Constitutional Court's ruling had significant positive implications for ensuring zakat as a socioeconomic instrument, thereby protecting it from profit exploitation. On the other hand, mobile applications and blockchain can digitalize zakat and improve its transparency and effectiveness, even though they face implementation challenges. This article emphasizes the state's role in zakat management and how technology can improve zakat administration. This study indicates that stronger government interventions are needed to promote the use of technology and improve zakat governance. Research on zakat, especially in light of the Constitutional Court's decision, should be a very important part of discussions on how to implement it and its regional effects, whilst exploring how digitalization can lead to greater transparency and cooperation.